Problem Studies and Skill Development Guidelines in Creating Online Media for Communication Arts Program Students in Rajabhat Universities, Northeast Thailand - Atijitta, Panisaya (Siam Communication Review, 2025)
This research aimed to explore the problems, needs, and guidelines for developing skills in creating online media for Communication Arts program students in the at Rajabhat Universities in Northeast Thailand. A mixed-methods research approach was used in this study. The quantitative data was collected through a survey of students from 10 Rajabhat Universities in the northeast region, involving 400 participants. The qualitative data was gathered through focus group discussions with representatives from faculty, students, graduate users, and graduates. The survey results revealed that 54.5% of the Communication Arts students aspired to pursue careers as online YouTubers, TikTokers, bloggers, influencers, or content creators. In terms of skill development needs, students expressed the highest need for skills in using image editing, graphic design, photo enhancement, and drawing (x̄ = 4.19, S.D. = .902). The focus group discussions revealed that stakeholders in the Communication Arts program identified the rapid changes in technology as a significant problem, leading to the quick obsolescence of learning support materials and the necessity to update instructors to keep pace with technological advancements. The suggested guidelines for developing online media creation skills among Communication Arts students included enhancing the curriculum to focus on utilizing technology for information gathering to create content, fostering creativity, and improving skills in online media usage and production for online platforms, as this aligns with modern job trends that cater to contemporary individuals and organizations.